Success and barrier factors in agile transformations - Batista, F.; Pereira, L.; Lopes da Costa, R. (International Journal of Agile Systems and Management, 2025)
Agile Methods have become an efficient way of working for organisations focused on delivering technological products. Despite the increased evidence on the success of Agile Transformations, scientific literature on this topic remains scarce. Quantitative methods were used to analyse the relation between Barriers and Success Factors and the importance of each one in explaining the success of an Agile Transformation. The results show that the Barriers Using old and new approaches side by side, Lack of coaching, Gap between short and long term planning and Reverting to the old way of working represent the Barriers that most contribute negatively to a successful Agile Transformation. The Success Factors Concentrate on agile values, Allow teams to self-organise, Recognise the importance of the Product Owner role, Communicate the change intensively, Educate management on Agile represent the Success Factors that most contribute positively to a successful Agile Transformation.